Quantitative functional imaging of VO2 metal-insulator transition through intermediate M2 phase. (15th August 2020) - Liu, Miao; Xie, Shaoxiong; Wei, Liyu; Galluzzi, Massimiliano; Li, Yuhao; Wang, Qingyuan; Zhou, Xiaoyuan; Wang, Yaping; Li, Jiangyu
Abstract: VO2 exhibits metal-insulator transition (MIT) accompanied by structural phase transformation between rutile R phase and monoclinic M1 phase, and an intermediate monoclinic phase M2 may also emerge, stabilized by strain. The evolution of microstructures and properties across phase transition is not only critical for understanding the nature of MIT, but also important for numerous device applications, yet they are quite challenging to characterize. Utilizing advanced atomic force microscopy (AFM) techniques in combination with polarized light microscopy, X-ray diffraction, and Raman spectroscopy, we map the microstructure evolution of VO2 when it is heated from room temperature M1 phase to high temperature R phase through intermediate M2 phase, and acquire functional imaging of VO2 spanning these three phases as well. These result in quantitative mapping of electric conduction and Young's modulus of VO2 in one-to-one correspondence to its domain patterns, especially those with austenite-martensite interface between M2 and R phases. Young's modulus of M1, M2, and R phase of VO2 are determined to be 95 GPa, 65-117 GPa, and 98-100 GPa respectively, and significant anisotropy is observed in M2 phase. Rigorous continuum analysis has also been carried out to analyze the complicated domain pattern, validating our experimental observations that match theoretical expectation well. Graphic abstract: Image, graphical abstract